STUDYING THE PROPERTIES OF CASSITERITE-BASED AND SILICON OPTICAL LAYER PHOTOCELLS (ResearchJet Journal of Analysis and Inventions, 2023)
The article describes the methods of studying the properties of cassiterite-based and silicon optical layer photocells.